Optimization of Sport Tourism Potential on Paramun Hill in Belitung Regency for Sustainable Tourism - Pratiwi, Yunisti; Emansyah , Fardi; Santri, Agi; Setiawan , Budi (JELAJAH: Journal of Tourism and Hospitality, 2025)
Sports tourism has become a rapidly growing trend in various countries, including Indonesia. Peramun Hill, which is located in Air Selumar Village, Sijuk District, Belitung Regency, has great potential to be developed as a sports tourism destination considering its natural beauty, biodiversity and supporting infrastructure. This research aims to identify the potential for sport tourism in Peramun Hill and formulate optimization strategies in its development to support the sustainability of tourism in this area. The research method used is a qualitative approach with a case study method, involving in-depth interviews, participant observation and literature study. The research results show that Peramun Hill has a landscape that supports various natural sports activities, such as hiking, rock climbing and mountain biking. Apart from that, community-based management and the use of digital technology in tourism provide added value for this destination. Recommended optimization strategies include improving trekking and hiking infrastructure, digital-based promotions, collaboration with influencers and travel agents, as well as organizing sustainable sporting events. The active participation of local communities and policy support from the government are also key factors in the successful development of sports tourism in Peramun Hill. With the right strategy, Peramun Hill has the potential to become a leading sports tourism destination that will not only increase the number of tourist visits, but also have a positive impact on the local economy and environmental conservation.